2006
DOI: 10.1017/s0022215106000879
|View full text |Cite
|
Sign up to set email alerts
|

A technique to identify and preserve the spinal accessory nerve during neck dissection

Abstract: Our method enables the surgeon to locate the nerve precisely and to avoid damage to it, thereby maximizing post-operative function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 5 publications
0
24
0
Order By: Relevance
“…Most describe preservation of SAN through its identification in the lower neck, near its entry at the anterior border of the trapezius muscle. 5 A lesser number of studies are available in literature describing the courses of SAN in relation to its surrounding structures in the upper neck region. 3,4,8 Different authors have reported variable relations of SAN with IJV in upper neck and most of these studies report a higher incidence of lateral relation of SAN to IJV compared with a medial relation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most describe preservation of SAN through its identification in the lower neck, near its entry at the anterior border of the trapezius muscle. 5 A lesser number of studies are available in literature describing the courses of SAN in relation to its surrounding structures in the upper neck region. 3,4,8 Different authors have reported variable relations of SAN with IJV in upper neck and most of these studies report a higher incidence of lateral relation of SAN to IJV compared with a medial relation.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,8 Different authors have reported variable relations of SAN with IJV in upper neck and most of these studies report a higher incidence of lateral relation of SAN to IJV compared with a medial relation. [3][4][5][7][8][9] There is a lot of variation in the incidence of lateral and medial relation in different studies with some reporting a very low percentage of medial relation. 3 Also there is variability in the results of cadaveric studies and those on live ND.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,8 Different authors have reported variable relations of SAN with IJV in upper neck, and most of these studies report a higher incidence of lateral relation of SAN to IJV compared to a medial relation. [3][4][5][7][8][9] There is a lot of variation in the incidence of lateral and medial relation in different studies with some reporting a very low percentage of medial relation. 3 Also there is variability in the results of cadaveric studies and those on live ND.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical significance of recognizing the position of the accessory nerve as it enters the lateral cervical region just superior to the nerve point of the neck is that its preservation in modified radical neck dissection, as might be performed to resect metastatic tumors or cervical lymph nodes, helps minimize subsequent shoulder dysfunction (Robbins and Samant, 2005;Chaukar et al, 2006;Salgarelli et al, 2009). It is also Nerve point of the neck and its relationship to the SCM muscle.…”
Section: Clinical Relevancementioning
confidence: 99%
“…Sections of the anterior scalene muscle, common carotid artery, and internal jugular vein were removed to expose the phrenic and vagus nerves. lateral cervical region) has been referred to as Erb's point (Robbins and Samant, 2005;Chaukar et al, 2006;Salgarelli et al, 2009). It is important, however, to appreciate that this is not the original intent of the term (Tubbs et al, 2007).…”
Section: Erb's Point-its Uses and Misusesmentioning
confidence: 99%